ANALYSIS OF FACTORS CONTRIBUTING TO DRUG DEALER RECIDIVISM AT THE CLASS IIB SEKAYU CORRECTIONAL FACILITY - Amanda, Alfani Putra; Jarodi, Odi (Universitas Nusa Cendana, 2025)
Drug dealer recidivism poses a significant challenge to the correctional system in Indonesia, where the complexities of internal and external factors often drive former inmates to re-offend. This study aims to identify the factors influencing drug dealer recidivism among inmates at the Class IIB Sekayu Correctional Facility. This research employs a qualitative method, collecting data through observations and interviews with inmates and correctional officers. Findings reveal that internal factors, such as psychological stress and low emotional management skills, along with external factors, such as social stigma and lack of family support, significantly increase the risk of recidivism. Additionally, correctional facilities face challenges in providing adequate rehabilitation services, lack of post-release support programs, and limited community involvement in the reintegration process. The conclusion indicates that sustained rehabilitation programs, strengthened family support, and synergy with external parties are essential to reducing recidivism rates. It is recommended that correctional facilities develop skill-based training and emotional support programs to facilitate more effective reintegration of inmates into society. Keywords: Recidivism; Drug Dealers; Rehabilitation; Family Support; Class IIB Sekayu Correctional Facility